Measuring self-reliance and wellbeing among forcibly displaced women enrolled in a gender-focused economic empowerment program: A protocol for a pilot randomized controlled trial in Colombia - Lindsay Stark; Ilana Seff; Adriana Monar; Diany Castellar; Neetu Mahi; Arturo Harker Roa (PLoS ONE, 2025)
Colombia currently hosts nearly three million Venezuelan refugees and migrants and is home to seven million internally displaced Colombians. For forcibly displaced populations in Colombia, and especially for women, gender-based violence (GBV) poses a threat during transit and in their new homes where xenophobia, lack of accessible and adequate services, limited safe economic opportunities, and lack of information on access to services, further increase risk. The dearth of livelihood opportunities also affects forcibly displaced populations, especially women. This study will conduct a randomized-controlled trial (RCT) of HIAS’ Entrepreneurship School with Gender Lens (ESGL), a program that targets forcibly displaced GBV survivors and women at-risk to help them develop business ideas, access needed support for the prevention of and response to GBV, and improve overall self-reliance. The RCT will be conducted within three cities in Colombia; approximately 80 eligible participants will be enrolled in each city and randomized to a treatment or control arm. Survey questionnaires will be administered to participants at baseline, eight months following baseline (endline), and 3–4 months after endline. Outcomes of interest include household self-reliance, mental health, resilience, empowerment, utilization of GBV services, and social support.